The Wraith - Marvin, Mike; Sheen, Charlie; Cassavetes, Nick; Fenn, Sherilyn; Quaid, Randy, 1953-; Barry, Matthew; Howard, Clint, 1959-; Platinum Disc Corporation (La Crosse, WI : Platinum Disc Corp., 2003)
Supernatural tale pitting The Wraith against a bizarre and brutal band of young, drag-racing delinquents who have been wreaking havoc on a small Arizona town.
Videodisc release of the 1986 motion picture.
MPAA rating: PG-13.
Music, Michael Hoenig, J. Peter Robinson ; executive producer, Buck Hougton ; editors, Scott Conrad, Gary Rocklen ; director of photography, Reed Smoot.
Charlie Sheen, Nick Cassavetes, Sherilyn Fenn, Randy Quaid, Matthew Barry, Clint Howard.
DVD.
Keywords: Supernatural -- Drama; Ghost plays; Juvenile delinquency -- Drama; Feature films; Horror films; Video (DVD)